SECURITY IMPLICATIONS FROM RIGHT-WING EXTREMISM AND TERRORISM IN EUROPEAN UNION (Security Dialogues, 2024)
This paper aim is an analyze how right-wing terrorism seeks to change the entire political, social and economic system to a right-wing extremist model. One cause for concern is the increasingly young age of suspects linked to violent online communities of varying degrees of organization. In this paper we draw attention that videogames and video game communication applications were increasingly used in 2020 for spreading rightwing terrorist and extremist propaganda, in particular among young people. In 2020, transnational sources of inspiration, such as the Siege culture, popularized in the virtual world, were observed to gain more traction especially with extremists that were younger in age than previously typical on the extreme right at national level. COVID-19 was observed to accelerate the trend of spreading right-wing extremist propaganda online, rather than offline. Right-wing extremists exploited COVID-19 to support their narratives of accelerationism and conspiracy theories featuring anti-Semitic, anti-immigration and anti-Islamic rhetoric. Also, they seek to extend their influence to other circles or sectors of activity (e.g., sports hooligans). In general, the right-wing extremist scene can be described as very heterogeneous, with differing manifestations in terms of organization, political objectives and the preferred means of achieving these. The right-wing extremist spectrum is a mixture of prejudices, contemptuous and totalitarian ideologies that, each in their own way, had security implications.